Analysis Of Vanilla Production And Sales Impact On The Welfare Of The Community In Suco Leimea Sorin Balu, Administrative Post Hatulia A, Municipality Of Ermera - de Vasconcelos, Nicolau (Jurnal Syntax Fusion, 2024)
This study aims to analyse the impact of vanilla production and sales on the welfare of the community in Suco Leimea Sorin Balu, Administrative Post Hatulia, Municipality of Ermera. The research method involves field surveys and data analysis to evaluate the relationship between vanilla production and the local community's well-being. The analysis results indicate that vanilla production and sales have a significant positive impact on community welfare, including increased income, access to public services, and economic empowerment. The implications of these findings are crucial in the context of local development and community economic empowerment. This study provides valuable insights into the economic contribution of vanilla to social well-being in the region.